Investigation of energy band gap and conduction mechanism of magnesium substituted nickel ferrite nanoparticles. Issue 9 (1st June 2017) - Chavan, Pradeep; Naik, L. R.
Abstract : Polycrystalline ferrite nanoparticles having the general formula Ni1 − x Mg x Fe2 O4 (in which magnesium content x = 0.0, 0.1, 0.2, 0.3, 0.4, and 0.5) were synthesized by auto combustion method. The formation of cubic spinel structure of Mg substituted nickel ferrites were confirmed by X‐ray diffraction (XRD) measurement with the space group of Fd3m ‐Oh 7 . The average particle size of the ferrites was determined by Scherrer formula; ranging from 41.41 to 45.93 nm. The lattice constant increases with increase in Mg concentration. The porosity of the ferrite samples was estimated using Hendricks and Adam's method; the porosity found to increase with an increase in Mg concentration. The decrease of DC electrical resistivity with an increase in temperature indicates the semiconducting nature of the ferrites. The decrease of dielectric constant with an increase in frequency was due to the hopping of free and localized electric charge carriers. The energy band gap of the ferrite nanoparticles were determined by Tauc plot and it was found to increase with an increase in Mg concentration (2.84 to 2.94 eV).